Report of a Meeting: An Expert Consultation on Body Composition and Adiposity for Children and Adolescents in All Their Diversity - Lauren E O’Connor; Lucero Lopez-Perez; Ricardo X Martinez; Maureen K Spill; Juan Pablo Peña-Rosas; Amanda J MacFarlane (Current Developments in Nutrition, 2025)
We convened experts to discuss methods for measuring body composition and diagnosing obesity among infants, children, and adolescents aged 0–19 y. The motivation for this meeting was to inform critical decisions for a systematic review protocol to assess the diagnostic test accuracy (DTA) of body mass index (BMI)-for-age and sex for diagnosing infants, children, and adolescents with excessive adiposity that can impair health. Thirty-nine clinicians and researchers from 23 countries provided written responses and/or attended 1 of 2 virtual meetings held in January 2024. Experts were asked to share their perspectives about methods and clinical tests used to measure body composition, including thresholds and adiposity types (i.e., total or central), for diagnosing obesity for infants, children, and adolescents. Experts suggested that deuterium oxide dilution, magnetic resonance imaging, dual energy X-ray absorptiometry, air displacement plethysmography, hydrostatic weighing, and multicompartmental models were acceptable to measure body composition, with the 4-compartmental model preferred. Waist circumference and bioelectrical impedance were preferred clinical tests to use either alone or in combination with BMI for diagnosing obesity; preferential use was country specific. Most experts preferred fat mass index (fat mass/height2) to % body fat as the metric, because it is more sensitive to changes over time and depends on age and height, similar to BMI. Experts agreed that total and regional adiposity are important for determining metabolic risk related to obesity, but using central adiposity for diagnosing obesity is challenging due to variations in body type. All agreed that age, race, ethnicity, and puberty stage should be considered when defining thresholds of obesity. This input from experts informed the systematic review protocol for an assessment of the DTA of BMI to support the World Health Organization’s guideline development for the integrated management of children and adolescents with obesity in all their diversity.